The syntactic Order and its Role in the Rhetoric - Mahmood Fotoohi Rudmajani (مطالعات زبانی و بلاغی)
The term "verse" in the Persian Dari literature refers to two meanings: one's poetry rhyme and another is syntactic. This essay describes the concept of order as aesthetic quality in syntax and separates it from the term "verse" meaning "poetry rhyme". First, it introduces the theory of order and descent; then, by explaining the two concepts of the basic order (constructive syntax) and the artistic order (constructive syntax), it tries to discuss the role of syntactic reciprocity in the process of artistic writing and the formation of literacy, and the value Reveal a recipe in literary language. Artistic dehumanization is achieved through the manipulation of a synonym for updating information. In this paper, the concept, syntactic dynamism is also considered as an aesthetic process in reading poetry.